Profil Pembudidaya Ikan Mas (Cyprinus carpio) dengan Sistem Minapadi di Kabupaten Toraja Utara - Fendjalang, Sophia N. M.; Pasanea, Alberthus D.; Pasanea, Krisye; Rijoly, Stefanno M. A. (University of Pattimura, 2024)
Fish farming is an activity that contributes to family income and welfare, where fishery commodities are produced in a controlled environment by utilizing the principles of aquatic ecosystems. Carp is the most popular freshwater fish commodity, so many of them are produced using the minapadi system. Therefore, this research aims to describe the profile of goldfish cultivators using the minapadi system and its potential in North Toraja Regency, South Sulawesi Province. This research was conducted in June 2023 in 5 sub-districts, namely Tikala, Rantepao, Sopai, Tondon, and Nanggala, North Toraja Regency, South Sulawesi Province. Data collection was carried out using respondent interview methods and field observations. Determining respondents was carried out using a purposive sampling method and the number of respondents was obtained using the snowball technique, where data was taken from 85 carp farmers using the minapadi system. The results of the research show that goldfish cultivators using the minapadi system in North Toraja Regency are predominantly aged 22-55 years, with a high school education, several family members of 1-9 people and 67.06% of cultivators have not/are not registered with KUSUKA status. For the potentian goldfish farms, farmers have their own land ownership status, farm area < 10,000 m2 to > 10,000 m2, minimum production of 20 kg/cycle to > 100 kg/cycle, and income of IDR. 1,000,000 to >Rp. 10,000,000 per year.